Phytochemical screening and antimicrobial potentials of Borreria sps (Rubiaceae) - Wong, K.Y.; Vikram, P.; Chiruvella, K.K.; Mohammed, A. (The Authors, 2015)
Successive hexane, acetone, ethanol and methanolic whole plant extracts of the Borreria sps were investigated for phytochemical screening and assessed for antimicrobial activity. Phytochemical analysis of Borreria sps extracts revealed the presence of phenolics, flavonoids and tannins. Among them, Borreria laevicaulis hexane extracts were found to be most effective showing the largest zone of inhibition against Staphylococcus aureus (22.15 mm) and Candida albicans (25.65 mm). Further studies indicated that the minimum inhibitory concentration of B. laevicaulis hexane extracts was found to be 62.5 μg/ml against S. aureus and 250 μg/ml against C. albicans and the zone of inhibitions was significantly higher than nystatin (positive control). Together, we provide new insights of the B. laevicaulis as a potential candidate for antimicrobial drug discovery using in vitro studies that might be useful to treat human infectious diseases and antibiotic resistant pathogens